Analisis Cacat Las SMAW dengan Elektroda Berbeda Posisi 2G pada Baja ST 37 Metode FTA - Iman Pradana A Assagaf; Ariyanto Ariyanto; Angger Bagus Prasetyo; Muhammad Aqdar Fitrah (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to analyze the types and causes of welding defects that occur during Shielded Metal Arc Welding (SMAW) using different electrodes in the 2G position on ST 37 steel. The research was conducted by students of the Diploma III Industrial Agro-Manufacturing Engineering Study Program at Politeknik ATI Makassar using both qualitative and quantitative approaches. A total of 10 welded samples were visually examined and tested using the liquid penetrant method to detect surface defects. The analysis employed the Fault Tree Analysis (FTA) method with a deductive approach to identify the top events representing major defect types, trace their root causes through the fault tree structure using AND and OR logic gates, and analyze the relationships among contributing factors. The results revealed five dominant defect types—spatter, stop-start, surface undercut, root concavity, and blow hole—which accounted for 61.7% of all detected defects. These defects were primarily caused by technical factors, including unstable arc control, improper welding angles and travel speeds, and poor cleanliness of electrodes and materials. Other defects, including root undercut, cold lap, excessive penetration, pin hole, and porosity, also affected weld quality. Based on the FTA findings, corrective actions were recommended, including operator retraining, proper parameter adjustment, equipment maintenance, and enhanced supervision to improve overall weld quality.